The Non-Physical Work Environment and Teacher Job Satisfaction as Pillars in Fostering Work Discipline Among Civil Servant Teachers at Public Junior High Schools in the City of Cirebon - Fifi Aulia Ramadhanty; Noveria Susijawati (Green Publisher Indonesia, 2026)
This study aims to analyze the influence of non-physical work environment and job satisfaction on teachers’ work discipline at public junior high schools in Cirebon City. The study used a quantitative method with an associative research design. The population included all public junior high school teachers in Cirebon City, and a sample of 90 teachers was determined using the Slovin formula combined with purposive sampling. Data were gathered via questionnaires and analyzed through multiple linear regression using SPSS version 29. The findings show that the non-physical work environment positively and significantly influences teachers’ work discipline, and job satisfaction also has a positive and significant impact on teachers’ work discipline. Furthermore, the non-physical work environment and job satisfaction jointly contribute significantly to teachers’ work discipline within a regression model. The coefficient of determination (R Square) of 0.616 indicates that 61.6% of the variation in teachers’ work discipline can be explained by the non-physical work environment and job satisfaction, while the remaining 38.4% is influenced by other factors outside this study. These findings suggest that improving teachers’ work discipline requires not only formal rules and monitoring systems but also a supportive non-physical work environment and a high level of job satisfaction. Therefore, schools should focus on enhancing these aspects to strengthen teachers’ work discipline sustainably.